Analysis of Land Carrying Capacity and Projected Rice Agricultural Land Needs in 2033 in Southeast Aceh Regency Aceh Province - Lubis, Muhammad Achbar; Lubis, Satia Negara; Nasution, Zulkifli (Universitas Medan Area, 2024)
The carrying capacity of agricultural land is defined as the ability of a region to provide land that can be used to support human agricultural activities. The Southeast Aceh Regency in Aceh Province requires an analysis of land carrying capacity to anticipate the sufficient food needs in the future. The Objective of this study is to analyze the carrying capacity of agricultural land and to analyze the need for paddy fields with a population projection approach for the next 10 years. The analytical method used in this study is quantitative descriptive analysis. The study reveals that, in 2023, the majority of the 16 districts in Southeast Aceh Regency have a predominant classification of Class II for agricultural land requirements. Generally, both land carrying capacity and agricultural land requirements are satisfactory.